Protein digestibility of Pajuro (Erythrina edulis Triana) seeds subjected to traditional cooking - DELGADO SORIANO, VICTOR DANIEL (2022)
The protein digestibility of pajuro seeds (Erythrina edulis Triana) was determined after the conventional cooking process. The processed seeds were dried, ground and incorporated into isoproteic and isocaloric diets for evaluation with Holtzman rats. The results were expressed in terms of means and standard deviations. A one-way analysis of variance (ANOVA) was performed with Tukey's multiple comparison test to determine significant differences (p <0.05) in the proximal composition values ​​and a correlation analysis between protein consumption / gains weight and feed intake / weight gain. A protein value of 20.58 was obtained in the cooked straw seeds, and values ​​of 25.89, 2.97 and 45.56 for feed consumption, weight gain and specific growth rate respectively. Regarding the protein quality indicators, a positive nitrogen balance was obtained with a value of 0.19, biological value of 65.52%, apparent digestibility of 67.44% and true digestibility of 76.74%; likewise, taking into account the presence of sulfur amino acids as limiting factors, a value of 0.36 was determined for the theoretical count of amino acids, a theoretical count of amino acids corrected for digestibility of 28 and a theoretical count of digestible essential amino acids of 26. These results place traditional cooking as an alternative to facilitate the consumption of pajuro seeds produced in the tropical Andes, thus improving its use and satisfaction of consumer needs; however, supplementation with other food sources or incorporation of synthetic amino acids is necessary to replace the presence of limiting amino acids.